2017
DOI: 10.1200/po.17.00063
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Metastatic Spread and Mechanisms of Resistance to Crizotinib in ROS1-Positive Non–Small-Cell Lung Cancer

Abstract: PURPOSE The ROS1 tyrosine kinase is activated through ROS1 gene rearrangements in 1–2% of non-small cell lung cancer (NSCLC), conferring sensitivity to treatment with the ALK/ROS1/MET inhibitor crizotinib. Currently, insights into patterns of metastatic spread and mechanisms of crizotinib resistance among ROS1-positive patients are limited. PATIENTS AND METHODS We reviewed clinical and radiographic imaging data of patients with ROS1- and ALK-positive NSCLC in order to compare patterns of metastatic spread at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
222
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 211 publications
(253 citation statements)
references
References 51 publications
5
222
0
6
Order By: Relevance
“…Notably, not all clinicopathologic features are shared between ALK - and ROS1 -rearranged NSCLCs. For example, one recent series comparing 39 ROS1 -rearranged and 196 ALK -rearranged NSCLC patients found that ROS1 rearrangements were associated with a significantly lower rate of extrathoracic and brain metastases at the time of diagnosis, in addition to a lower cumulative incidence of brain metastases (42). Although the number of patients included in this series was limited, particularly for the ROS1 -rearranged subset, the findings suggest that patterns of metastases may be distinct for ROS1 - versus ALK -rearranged lung cancer.…”
Section: Clinicopathologic Characteristics Of Ros1-rearranged Lung Camentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, not all clinicopathologic features are shared between ALK - and ROS1 -rearranged NSCLCs. For example, one recent series comparing 39 ROS1 -rearranged and 196 ALK -rearranged NSCLC patients found that ROS1 rearrangements were associated with a significantly lower rate of extrathoracic and brain metastases at the time of diagnosis, in addition to a lower cumulative incidence of brain metastases (42). Although the number of patients included in this series was limited, particularly for the ROS1 -rearranged subset, the findings suggest that patterns of metastases may be distinct for ROS1 - versus ALK -rearranged lung cancer.…”
Section: Clinicopathologic Characteristics Of Ros1-rearranged Lung Camentioning
confidence: 99%
“…Mutations within the ROS1 kinase domain occur in ~50–60% of crizotinib-resistant tumors (42). This is higher than the frequency of ALK kinase domain mutations (~20–25%) observed in crizotinib-resistant ALK -rearranged lung cancers (60, 61), and may reflect differences in crizotinib binding characteristics or its higher potency against ROS1 versus ALK (55).…”
Section: Ros1-targeted Therapies In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Brain and meningeal sites of disease both at diagnosis and after first-and second-generation inhibitors represent a critical issue in ALK-positive patients and, to a lower extent, in ROS1-positive ones (10). Although the sites of disease progression before lorlatinib were not recorded in the study, we can easily speculate that a significant proportion of ALK-rearranged NSCLC patients had previously developed central nervous system (CNS) progression.…”
Section: Editorialmentioning
confidence: 91%
“…A number of secondary ROS1 resistance mutations have been identified, with the most common being G2032R in approximately 40% of crizotinib-treated patients (75). More recently, entrectinib, a novel multikinase inhibitor, has demonstrated robust PFS of 30 months in a small cohort of patients with ROS1-positive NSCLC (76).…”
Section: Modifications Of the Oncogenic Drivermentioning
confidence: 99%